PEMBUATAN PETA SITUASI SKALA 1 : 500 DUSUN PANDANREJO DAN DUSUN TEGALMIRI DESA BANYURIPAN KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , DEVI AGUSTIANI S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of this final project is to report the activities of terrestrial surveying and land mapping in the field work. The pratical work was started from April 14th to 26th, 2014 in Pandanrejo and Tegalmiri area, Banyuripan village, Bayat sub-district, Klaten regency, Central Java province. The method was the manufacturing of the mapping control framework which are consisted of the horizontal control framework survey by using the polygon method and vertical control survey that used the waterpass method, planimetric detail and high detail measurement, and also digital mapping. The result obtained the presentation of a map of the situation in spatial data of the Earth surface in Pandanrejo and Tegalmiri area, Banyuripan village, Bayat sub-district, Klaten regency, Central Java province. The situation map presentation of planimentric detail and high detail, high details were presentation by countour from elevation interpolation of high detils. The map used 1:500 scale in UTM projection system (Universal Transverse Mercator). The author of this final project revealed that had obtained experiences of surveying and land mapping of terrestrial measurement as well as how to work in teams in a professional manner.